Drivers human resources 4.0: Technological, organisational & environmental of human resources 4.0 at Malaysian private companies - Muhammad Shabir, Shaharudin; Wahida Najiha, Zulkifli; Gui, Anderes; Fernando, Yudi (Penerbit Universiti Malaysia Pahang, 2021)
This study aims to evaluate and measure the Driver of Human Resources 4.0: Technology, Organization and Environment. Besides that, the study also suggests the better Driver Human Resources 4.0 to increase at the company in future. Meanwhile, these research objectives were found 1) to identify the relationship between technological drivers with Human resource 4.0. 2) To investigate the relationship between organisational drivers with Human resource 4.0. 3) to analyse the relationship between environmental drivers and Human resource 4.0. The theoretical model used was the Technology-organization-environment (TOE) Theory. The methodology for this research that has a quantitative method using a questionnaire survey by google form with has five (5) Likert scales. The questionnaire surveys by google form were sent to Malaysian private companies. This research used descriptive statistical analysis convergent validity and mean value analysis, correlation testing, which have been automatically generated by Smart PLS software version 3.3.2 statistical software to test the hypothesis for this research. From the tests that have been conducted, Driver Human Resources 4.0: Technology, Organization and Environment are the variables that affect the Human Resources in happening in Malaysian Public Companies. At the end of the study, the research questions were answered, and specific recommendations were made for the case technology. The most efficient recruiting networks have been identified as a result of this research, the most appropriate selection strategies have been suggested, and adequate retention techniques have been explored. In addition, some additional ideas have been given for future research for example the sense of accelerating the pace of transition, organizational factors may play a major role in the creation of an environment conducive for learning and innovation in a company nowadays.